STRATEGI DAKWAH KANTOR URUSAN AGAMA DALAM MENGUBAH POLA PIKIR MASYARAKAT DI KECAMATAN WATANG SAWITTO KABUPATEN PINRANG (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2022)
The results showed that: 1. The application of the KUA da'wah strategy in changing the mindset of the community towards the applicable regulations at KUA by applying the da'wah method through wisdom, Mau'idzatil Hasanah, Mujdalam Billati Hiya Ahsan as a propaganda strategy for KUA Watang Sawitto. 2. Challenges and opportunities in implementing the KUA da'wah strategy in changing people's mindsets are a) The challenges faced in implementing the KUA da'wah strategy come from different (low) education levels and come from community traditions/habits. b) The opportunity that is obtained when implementing the da'wah strategy in changing the mindset of the community is the realization of a more Islamic society that upholds the spirit of Ukhuwah Islamiyah. The implication of the research is in the da'wah strategy of changing people's mindsets towards the regulations in force at the Office of Religious Affairs. Those who apply the da'wah method through oral, Bil Qalam and Bil Haal. This method has been implemented well although there are some advantages and disadvantages. By applying the da'wah method, the people's mindset will gradually understand more about Islam. In this case, the community should comply more with the regulations of the Office of Religious Affairs so that the community understands more about Islam and applies Islamic values in daily life, and leaves old habits/culture